Continuous counting, sizing and refractive index measurement of airborne particles in hollow-core photonic crystal fibre - Sharma, Abhinav; Xie, Shangran; Zeltner, Richard; Russell, Philip St. John (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Air pollution by particles of aerodynamic diameter less than 2.5 μm (PM2.5) is currently an important environmental issue. As standard methods for monitoring and characterization are time-consuming and expensive, there is need for a simple, effective and inexpensive device for real-Time PM2.5 monitoring. Although optical methods based on the scattering of laser beams exist, they do not provide independent measurement of particle size and refractive index. In systems based on detection in an evanescent optical field, particles tend to adhere to the surface, strongly limiting the device lifetime. Here we report a new approach to airborne particle characterization that makes use of hollow-core photonic crystal fibre (HC-PCF). Employing optical gradient and radiation forces to trap and propel airborne particles along the hollow core, it provides in situ particle counting, sizing and refractive index measurement in real-Time with effectively unlimited device lifetime. We show that the transmission drop and time-of-flight can be unambiguously mapped to particle size and refractive index.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Optical trapping and manipulation; Photonic crystal fibre; PM

High-Precision Localization of Trapped Microparticles inside Hollow-Core Photonic Crystal Fibers using Coherent Optical Frequency Domain Reflectometry - Köppel, Max; Sharma, Abhinav; Renner, Esther; Xie, Shangran; Schmauß, Bernhard; Russell, P. St J. (2019 IEEE SENSORS, 2020)
We present a localization technique for an optically trapped microparticle inside hollow-core photonic crystal fibers which is the basis of a new generation of fiber optical sensors. A polystyrene particle of diameter 15 µm is optically trapped and moved inside the hollow-core fiber by optical forces while its position is tracked using coherent optical frequency domain reflectometry. We demonstrate that this technique can locate the particle position with a standard deviation of 10 µm. By applying a time-apertured Fourier transform, the dynamics of particle motion can be resolved with millisecond temporal resolutio

On-the-fly particle metrology in hollow-core photonic crystal fibre - Sharma, Abhinav; Xie, Shangran; Zeltner, Richard; Russell, Philip St. John (Optics Express, 2019)
Efficient monitoring of airborne particulate matter (PM), especially particles with aerodynamic diameter less than 2.5 µm (PM2.5), is crucial for improving public health. Reliable information on the concentration, size distribution and chemical characteristics of PMs is key to evaluating air pollution and identifying its sources. Standard methods for PM2.5 characterization require sample collection from the atmosphere and post-analysis using sophisticated equipment in a laboratory environment, and are normally very time-consuming. Although optical methods based on analysis of scattering of free-space laser beams or evanescent fields are in principle suitable for real-time particle counting and sizing, lack of knowledge of the refractive index in these methods not only leads to inevitable sizing ambiguity but also prevents identification of the particle material. In the case of evanescent wave detection, the system lifetime is strongly limited by adhesion of particles to the surfaces. Here we report a novel technique for airborne particle metrology based on hollow-core photonic crystal fibre. It offers in situ particle counting, sizing and refractive index measurement with effectively unlimited device lifetime, and relies on optical forces that automatically capture airborne particles in front of the hollow core and propel them into the fibre. The resulting transmission drop, together with the time-of-flight of the particles passing through the fibre, provide unambiguous mapping of particle size and refractive index with high accuracy. The technique offers unique advantages over currently available real-time particle metrology systems, and can be directly applied to monitoring air pollution in the open atmosphere as well as precise particle characterization in a local environment such as a closed room or a reaction vessel.
CRIS-Team Scopus Importer:2019-12-10

Tumbling and anomalous alignment of optically levitated anisotropic microparticles in chiral hollow-core photonic crystal fiber - Xie, Shangran; Sharma, Abhinav; Romodina, Maria; Joly, Nicolas; Russell, Philip St. John (Science Advances, 2021)
The complex tumbling motion of spinning nonspherical objects is a topic of enduring interest, both in popular culture and in advanced scientific research. Here, we report all-optical control of the spin, precession, and nutation of vaterite microparticles levitated by counterpropagating circularly polarized laser beams guided in chiral hollow-core fiber. The circularly polarized light causes the anisotropic particles to spin about the fiber axis, while, regulated by minimization of free energy, dipole forces tend to align the extraordinary optical axis of positive uniaxial particles into the plane of rotating electric field. The end result is that, accompanied by oscillatory nutation, the optical axis reaches a stable tilt angle with respect to the plane of the electric field. The results reveal new possibilities for manipulating optical alignment through rotational degrees of freedom, with applications in the control of micromotors and microgyroscopes, laser alignment of polyatomic molecules, and study of rotational cell mechanics.
CRIS-Team Scopus Importer:2021-07-30